Predation on pupa of Chrysomya rufifacies (Marquart) (Diptera: Calliphoridae) by parasitoid, Exoristobia philippinensis Ashmead (Hymenoptera: Encyrtidae) and Ophyra spinigera larva (Diptera: Muscidae). - Chin, H.C.; Ahmad, N.W.; Lim, L.H.; Jeffery, J.; Omar, B.; Dhang, C.C.; Weng, L.K.; Sofian-Azirun, M. (Malaysian Society of Parasitology and Tropical Medicine, 2009)
A forensic entomological study was conducted using monkey carcasses (Macaca fascicularis Raffles) that were placed in either an outdoor or indoor environment at a coastal area in Tanjung Sepat, Selangor, Malaysia during May until August 2008. We collected pupae of Chrysomya rufifacies (Marquart) from the carcasses and kept them individually. The emergence of 13 parasitic microhymenopteran, from one of the pupae occurring within a week were identified as Exoristobia philippinensis Ashmead (Hymenoptera: Encyrtidae). Another observation was made whereby a pupa of C. rufifacies was predated by a muscid larva, Ophyra spinigera (Stein). The larva squeezed into the pupa and consumed the contents. This paper report C. rufifacies as a new host record for E. philippinensis in Malaysia and highlighted the predatory behavior of O. spinigera larva in natural environment.